Survey Of Students' Lay Up Skills Level On Basketball Games At SMP Negeri 2 Seluma - Erik Selta Sahputra; Azizatul Banat; Supriyanto Supriyanto (Penerbit Jurnal Indonesia, 2021)
Generally, the most frequent and most popular sport in Indonesia is game sports, such as basketball. Basic techniques in basketball games such as dribbling, passing, and shooting in order to be successful in playing basketball. Among the several types of shooting above, the percentage of balls that enter with this lay up shoot technique is large compared to other shooting techniques. This study aims to determine the level of students' lay-up skills in basketball games at SMP Negeri 2 Seluma. The place of this research was carried out on the basketball court of SMP Negeri 2 Seluma, the time of this research was carried out for 1 month, namely in June-July 2021 in accordance with the Research Permit. This research is a quantitative descriptive study using a survey method. Based on the results of the study, it can be concluded that after measuring the level of lay-up skills in the basketball game at SMP Negeri 2 Seluma, 16 of 30 students were in the very good category (53.33%). A total of 3 people in the moderate category (10%). A total of 5 people in the low category (16.67%). A total of 6 people in the very low category (20%).